Would-be great powers, status, and stigma: the case of Brazil, 1970-1979 - De Bhal, J (2020)
This thesis critically engages the dominant theoretical account of would-be great power status-seeking behaviour in International Relations (IR), namely Larson and Shevchenko’s social identity theory (SIT) framework. This critical engagement involves bringing the SIT framework into dialogue with a literature that it has hitherto neglected: the emerging scholarship on stigma in IR. Through this dialogical synthesis, I make two theoretical arguments.